Segmenting the Impact of Organizational Structure and Leadership on Project Resilient and Project Success in the Ethiopian Construction Industry: a FIMIX-PLS & PLS-POS Approach - Bekele Desta, Kebede; Lunga, Msengana (International Journal of Engineering and Management Sciences, 2025)
This research looks at the vital roles of leadership and organisation design in the attainment of project resilience and success in the construction sector. Informed by contemporary theories on organisational resilience and leadership, a framework was developed and rigorously tested against data using Partial Least Squares Structural Equation Modelling (PLS-SEM) and with more advanced techniques of segmentation (FIMIX-PLS and PLS-POS) to identify and take into consideration unobserved heterogeneity. Using data collected from project professionals, resilient leadership and adaptive organisation design were shown to be critical to project resilience, but the effect of leadership and organisation design on project resilience differed from segment to segment as well as across demographics. The ex-post analysis suggested that the awareness of resilience, practical experience and higher education exacerbated the relationships between aspects of resilient leadership and project resilience, as well as between adaptive organisation design and project resilience. The analysis also showed that relationships between leadership, organisational structure, and resilience can be mediated by demographic factors, such as awareness, experience, and education. The findings highlighted the importance of fostering inclusive, participative type leadership styles and continuous forms of experiential learning to enhance resilience outcomes. The value of specific indicators such as team participation in decision making or the leader’s self-confidence was also identified as being critical aspects of resilient organisational structures and effective leadership. The implications of this study were important for each group of stakeholders: organisations should encourage resilience-based leadership, experiment with multi-dimensional flexible team structures and create a culture of continued, experiential learning and communications as knowledge and industries evolve. The theoretical contributions that validated the effects of segments of latent variables and offered insight into the added value of using segmentation were positive contributions to theory. Limitations, such as sample size and sector, stimulate avenues for future work and in particular reinforce the case for longitudinal, cross-sector research to build sectors’ internal and external constructs of project resilience. Future research needs to apply multi-facilitated empirical, qualitative and advanced analytics means to enable further quantification, and complexity in project survival, success and resilience.